Nachwuchs-Café: Symposium zur interdisziplinären Vernetzung von Doktorand/ innen und Postdocs - Rumlich, Dominik; Matz, Frauke (Grenzen, Grenzräume, Entgrenzungen)

Reliabilität - Rumlich, Dominik (Leistungsmessung, Evaluation und Feedback im Fremdsprachenunterricht)

Starting early or late? Parental perspectives on the onset of English language education at primary school in Germany - Rumlich, Dominik; Porsch, Raphaela (Early language education in instructed contexts)
Abstract This study investigates parents’ perspectives on the preferred onset of English education in Germany and potential explanatory factors drawing on a cross-sectional survey of 2,645 parents from the EUBE project ( E nglisch u nterrichts b eginn aus E lternsicht / Parental perspectives on the onset of English Language Education). Results reveal that a significant majority of parents advocate for an early start in year 1 or 2 of primary school, generally aligning with their strong conviction of the importance of English, high educational aspirations and expectations, and their own (early) start of language education. The findings contribute to a deeper understanding of parental perspectives that have also shown to be related to multiple indicators of educational success in general and achievements in language learning in particular.

DigiLex — A Checklist for the Evaluation of Digital Tools for Second and Foreign Language Lexical Learning - Lehmkuhl, Paulina; Wagner, Benedikt; Frisch, Stefanie; Rumlich, Dominik; Visser, Judith (TESOL Journal)
ABSTRACT The use of digital tools for second and foreign language lexical learning is increasingly popular and research in this area is constantly expanding. However, little has been written about specific criteria that could be used to identify tools with high‐quality lexical input, as available checklists and frameworks for digital media tend to neglect detailed analyses of the vocabulary domain. This article addresses this issue by presenting the Checklist for Evaluating Digital Resources for Lexical Learning (DigiLex), which combines important digital language learning criteria with an extensive evaluation of lexical content. The checklist is both theory‐based and user‐friendly, aiming to fill a gap between theory and practice in the field of digital lexical learning. The article discusses the theoretical basis of the checklist and integrates the results of a small pilot study with pre‐service and in‐service teachers, emphasizing feasibility in everyday learning and teaching. By providing an easy‐to‐use tool for identifying suitable digital resources, the DigiLex checklist aims to support language learners and teachers in self‐regulated lexical learning.

Kompetenzen für den erfolgreichen Übergang von der Sekundarstufe I in die berufliche Ausbildung sichern. Gutachten der Ständigen Wissenschaftlichen Kommission der Kultusministerkonferenz - Becker-Mrotzek, Michael; Efing, Christian; Gerick, Julia; Greefrath, Gilbert; Hammann, Marcus; Hannover, Bettina; Heckhausen, Jutta; Jost, Jörg; Keller, Stefan; Leiß, Dominik; Leutner, Detlev; Lewalter, Doris; et al.

Maximizing linguistic and cognitive potential: the role of vocal training with pop songs in teaching English as a foreign language - Vivone, Antonio; Rumlich, Dominik; Lehmann-Wermser, Andreas (Learning: Research and Practice)

CLIL-related benefits for general EFL proficiency - Rumlich, Dominik (The Cambridge Handbook of multilingual education)

Feedbackkompetenz handlungsnah prüfen: Die Entwicklung einer rollenspielbasierten Simulation als Prüfungsformat für angehende Englischlehrkräfte - Janzen, Thomas; Vogelsang, Christoph; Rumlich, Dominik (Wissen, Können und Handeln von Fremdsprachenlehrpersonen)

Beginn des Englischunterrichts aus Sicht von Eltern - Rumlich, Dominik; Porsch, Raphaela; Brunsmeier, Sonja (Zeitschrift für Fremdsprachenforschung)

Starting early? Ergebnisse einer Elternbefragung zum Beginn des Englischunterrichts - Rumlich, Dominik; Porsch, Raphaela; Brunsmeier, Sonja (Grundschule Englisch)

Die mündliche Prüfung. Eine Einführung - Matz, Frauke; Rogge, Michael; Rumlich, Dominik

Deskriptive Statistik - Rumlich, Dominik

Inferenzstatistik - Rumlich, Dominik

Show, don't tell - Rollenspielbasierte Simulationsprüfungen für zukünftige Englischlehrkräfte (Poster) - Janzen, Thomas; Meier, Jana; Rumlich, Dominik; Vogelsang, Christoph; Wotschel, Philipp (30. DGFF Kongress 2023)

Attention to diversity in German CLIL classrooms: Multi-perspective research on students’ and teachers’ perceptions - Siepmann, Philipp; Rumlich, Dominik; Matz, Frauke; Römhild, Ricardo (International Journal of Bilingual Education and Bilingualism)

Exploring the importance of prior knowledge and verbal cognitive abilities for foreign language learning - Rumlich, Dominik (Cognition and second language acquisition)

Attitudes of German high school students toward different varieties of English - Meer, Philipp; Hartmann, Johanna; Rumlich, Dominik (Applied Linguistics)

Weniger Kompetenz, mehr Resonanz. Contra Position - Rumlich, Dominik (Fremdsprachen Lehren und Lernen)

Nachwuchs-Café (reloaded): Standortbestimmungen - Rumlich, Dominik; Matz, Frauke (Standortbestimmungen in der Fremdsprachenforschung)

Between theory and practice: Rollenspielbasierte Simulationen als Prüfungsformat für handlungsnahe Feedbackkompetenzen angehender Englischlehrkräfte - Janzen, Thomas; Vogelsang, Christoph; Rumlich, Dominik (Professionstagung 2022)